Meningkatkan Hasil Belajar Siswa Pada Pokok Bahasan Bilangan Pangkat Dua Dengan Model Pembelajaran Open-Ended - Hasni Suciawati (JURNAL MATHEMATIC PAEDAGOGIC, 2020)
ABSTRACT This research is a type of classroom action research (CAR) with Open-ended Model learning in mathematics. The main problem in this study is the low learning outcomes of fifth grade elementary school students on material second squares. One of the teacher's efforts to improve student learning outcomes is to use an Open-ended learning model that is expected to improve student learning outcomes on the subject of the second rank in class V SD Negeri 023905 North Binjai North Academic Year 2019/2020. The subjects of the study were the fifth grade students of SD Negeri 023905 Binjai Utara with 26 students consisting of 14 male students and 12 female students. This research was conducted in two cycles with the same time, 2 × 35 minutes. As an object is the use of the Open-ended learning model, on the subject of second squares in class V SD Negeri 023905 North Binjai Academic Year 2019/2020. Data collection techniques used were observation sheets and tests. The results of the study in the first cycle obtained an average value of 57 students, who completed the KKM score of 14 students with a percentage of 53.84%, while 12 students who did not complete with a percentage of 46.15% of 26 students, due to the number of students classically not complete, then proceed to the next cycle. In cycle II the average value of students was 77, those who completed the KKM were 23 students with a percentage of 88.46%, while those who did not complete were 3 students with a percentage of 11.53% of 26 students. Based on the results of data analysis, it was concluded that student learning outcomes improved on the subject of the second rank with the Open-ended learning model in class V of SD Negeri 023905 North Binjai in the 2019/2020 Academic Year. Keywords: Learning Outcomes, Open-ended Learning Model